Campaigns, Governance and Urban Identity - BARRIENTOS AGUILAR CRISTOPHER ALEXI (Graduate School of International Studies Ajou University, 2024)
This study delves into Seoul, South Korea, as its primary focus. It investigates Seoul's journey from an industrial stronghold to a worldwide epicenter of technology and culture, meticulously tracing the historical path of city branding within Korea. By highlighting the essential contribution of cultural heritage to shaping Seoul's identity, it builds upon earlier arguments and aligns with the importance of branding symbols like 'Haechi' and campaigns such as 'Hi Seoul,' 'I Seoul U,' and 'Soul my Seoul.' The methodology involves conducting surveys with Korean residents, foreigners residing in Korea, and expatriates abroad, as well as interviews with specialists actively engaged in promoting Seoul and Korea. Through these surveys and interviews, the research aims to gain insights into the perceptions and attitudes of various stakeholders toward Seoul's branding initiatives, with special attention paid to evaluating the effectiveness of branding campaigns in resonating with local sentiments and aligning with Seoul's cultural identity. Findings from these surveys and interviews will inform policymakers about the importance of crafting locally resonant city branding strategies amidst globalization trends.
학위논문(석사)--국제개발협력과,2024. 8
Keywords: International Development and Cooperation city branding case of seoul